Circulating Fetuin-A and Risk of All-Cause Mortality in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Zhou, Zhongwei; Ji, Yuqiao; Ju, Huixiang; Chen, Hongmei; Sun, Mingzhong (Frontiers in Physiology, 2019)
Background: Investigations on the association of circulating fetuin-A with all-cause mortality risk in patients with chronic kidney disease (CKD) are conflicting. This meta-analysis aimed to provide a comprehensive estimation of the relationship between fetuin-A and all-cause mortality in CKD patients. Methods: A systematic literature search was performed in PubMed, EMBASE and The Cochrane Library up until 12 December 2018. Hazard risk (HR) and 95% confidence interval (CI) were pooled using random-effect or fixed-effect model models. Results: A total of 13 studies comprising 5169 CKD patients were included in the meta-analysis. In a comparison of individuals in the bottom third versus the top third of baseline fetuin-A levels, the pooled multivariate-adjusted HR for the risk of all-cause mortality was 1.92 (95% CI 1.31-2.80), and the significant association was observed only in dialysis patients, but not non-dialysis patients. When fetuin-A was treated as continuous variables, per 0.1 g/L increase of fetuin-A levels was associated with a 8% lower mortality risk in dialysis patients (HR 0.92, 95% CI 0.87-0.97, p=0.001), but per 0.01 g/L was not. Sensitivity analysis indicated the association was not adjusted by diabetes and inflammation. Conclusion: lower fetuin-A levels are associated with an increased risk of all-cause mortality independent of diabetes and inflammation in dialysis patients, and there may be a dose-response relationship between them.